Hermeneutika Modern: Sebuah Pengenalan Awal (II) - Kusmana Kusmana (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
The development of knowledge represents the dialectic of social dynamics and knowledge itself, even theology. From there arises various knowledge that later crystallizes into science. One of them is hermeneutics. It is a science that can be simply interpreted as the science of interpretation. This science initially served as a prerequisite for unraveling religious texts that were considered final and sacred. That is why hermeneutics as a science is closely related to the world of theology, specifically the sub-discipline of theology that deals with the methodology and authentication in interpreting the Scriptures in the Christian and Jewish traditions. This paper describes modern hermeneutics from the perspective of understanding, history, and its divisions into methodological, philosophical, and critical hermeneutics.